1997
DOI: 10.1016/s0895-7061(97)00271-9
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Modulates Monocyte Migration

Abstract: Migration of monocytes into the subendothelial space of the aorta has been considered to be an important event in the development of atherosclerosis. Because hypertension is commonly associated with atherosclerosis, we studied the effect of applied pressure on the migration of monocytes. Direct applied pressure increased the migration (P < .001) of monocytes across a filter when compared with normal atmospheric pressure. The migration of monocytes was found to be directly related to the amount of the applied p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
1
13
0
1
Order By: Relevance
“…[44][45][46] Activated platelets stimulate the production of monocyte chemotactic protein-1 by monocytes through enhanced chemokine secretion and direct platelet-monocyte contact, which is mediated by expression of P-selection on the platelet surface. 47 Such a mechanism leading to enhanced expression of monocyte chemotactic protein-1 in leukocytes has recently been found in acute myocardial infarction patients.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] Activated platelets stimulate the production of monocyte chemotactic protein-1 by monocytes through enhanced chemokine secretion and direct platelet-monocyte contact, which is mediated by expression of P-selection on the platelet surface. 47 Such a mechanism leading to enhanced expression of monocyte chemotactic protein-1 in leukocytes has recently been found in acute myocardial infarction patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports suggest that mechanical stimuli, such as extracellular pressure and repetitive strain, may alter other aspects of macrophage functions (25,34). Pressure (40 -130 mmHg) increases monocyte migration in a dose-dependent manner and enhances scavenger receptor expression in macrophages (44,55); increased pressure (40 -90 mmHg) has been shown to increase aggregated IgG uptake in mouse macrophage J774.16 cells (34), and extracellular pressure modulates the release of proinflammatory cytokines from human monocytic cells (50). Mechanical strain augments matrix metalloproteinase (MMP)-1 and MMP-3, but not MMP-9, expression in PMA-treated human monocytes or macrophages (63).…”
mentioning
confidence: 99%
“…There has been increasing interest in the effect of cyclic mechanical strain on cells in the skeleton, with several methods of investigation being described 18,29,30 and fluid flow has also been postulated as an important mechanism in other types of cell including osteoblasts. 31,32 Various methods have also been used to investigate the effect of changes in pressure on cells, 16,20,21 but there have been few investigations of the effect of changes in cyclic pressure. KleinNulend et al 17 showed that cyclic pressure influenced the metabolism of chondrocytes in an organ culture; the pressure was applied using a pump from a storage vessel.…”
Section: Discussionmentioning
confidence: 99%
“…This prevented the strain effect which was found to cause detectable changes in chondrocytes with the system of Wright et al 16 They found that chondrocytes failed to respond to the levels of cyclic pressure applied in these experiments in the absence of strain. Mattana et al 19 and Singhal et al 20 have made several studies of the effect of applied pressure on macrophages. They showed that small applied pressures resulted in increases in uptake of IgG by macrophage-like cells but that cyclic strain caused a decrease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation